An outbreak of high-level azithromycin resistant Neisseria gonorrhoeae in England. (24th November 2015) - Chisholm, Stephanie A; Wilson, Janet; Alexander, Sarah; Tripodo, Francesco; Al-Shahib, Ali; Schaefer, Ulf; Lythgow, Kieren; Fifer, Helen
Abstract : Objectives: To investigate a potential outbreak of high-level azithromycin resistant (HL-AziR) gonococcal infections diagnosed in eight patients attending a sexual health clinic in Leeds, North England, between November 2014 and March 2015. Methods: Eight cases of infection with gonococci exhibiting azithromycin minimum inhibitory concentrations (MICs) ≥256 mg/L were identified from patients in Leeds as part of the routine service provided by the Sexually Transmitted Bacteria Reference Unit. All patient records were reviewed to collate epidemiological and clinical information including evaluation of patient management. Whole-genome sequencing (WGS) was performed on seven gonococcal isolates to determine Neisseria gonorrhoeae multiantigen sequence type (NG-MAST), WGS comparison and mutations in the 23S rRNA genes. Results: All patients were heterosexual (five male, three female) from a range of ethnic backgrounds and from the Leeds area. Three patients were linked by partner notification. All patients were infected at genital sites and two women had pharyngeal infection also. Six patients received the recommended first-line therapy for uncomplicated gonorrhoea, one was treated for pelvic inflammatory disease and one received spectinomycin followed later by ciprofloxacin. Test of cure was achieved in seven patients and confirmed successful eradication. All seven isolates sequenced were identical by NG-MAST and WGS comparison, and contained an A2143G mutation in all four 23S rRNA alleles. Conclusions: Epidemiological and microbiological investigations confirm that an outbreak of a gonococcal strain showing HL-AziR is ongoing in the North of England. Every effort should be made to identify and curtail dissemination of this strain as it presents a significant threat to the current recommended front-line dual therapy.